A model of chronic IgE-mediated food allergy in ovalbumin-sensitized mice - Saldanha,J.C.S. (2004)
Food allergy is most frequently the result of IgE-mediated hypersensitivity reactions. Here, we describe a chronic model in which some of the intestinal and systemic consequences of continuous egg white solution ingestion by ovalbumin-sensitized eight-week-old BALB/c mice, 6 animals per group, of both sexes, were investigated. There was a 20% loss of body weight that began one week after antigen exposure and persisted throughout the experiment (3 weeks). The sensitization procedure induced the production of anti-ovalbumin IgG1 and IgE, which were enhanced by oral antigen exposure (129% for IgG1 and 164% for IgE, compared to sensitization values). Intestinal changes were determined by jejunum edema at 6 h (45% Evans blue extravasation) and by a significant eosinophil infiltration with a peak at 48 h. By day 21 of continuous antigen exposure, histological findings were mild, with mast cell hyperplasia (100%) and increased mucus production (483%). Altogether, our data clearly demonstrate that, although immune stimulation was persistently occurring in response to continuous oral antigen exposure, regulatory mechanisms were occurring in the intestinal mucosa, preventing overt pathology. The experimental model described here reproduces the clinical and pathological changes of mild chronic food allergy and may be useful for mechanistic studies of this common clinical condition.